Assessment of portuguese community forestry: using the Voluntary Guidelines on the Responsible Governance of Tenure and FAO community-based forestry framework - Skulkska, I. (2019)
In the last five decades, Community-Based Forestry (CBF) has become a subject of special attention. It is assumed that the transfer of rights to local communities will improve forest management. In Portugal more than 13% of the forest area belongs to local communities (termed baldios). Following FAO tools, assessments of Forest Tenure and CBF were conducted to evaluate the effectiveness of four baldio management types. The results revealed the most common challenges for baldios, vis- a-vis, rights associated with their management, protection of these rights, weak land administration, weak mechanisms for conflict resolution, problems with decentralized state support, cash flow management, and environmental challenges leading to wildfires, loss of biodiversity, and inadequate control of pests and invasive species. Resolution of these challenges is urgently needed at the legal, administrative and local levels. Future research should include assessments of CBF in other European countries to reduce the existing knowledge gap